Physical Fitness Levels of Students in Public Elementary School 8 Semende Darat Laut (Implementation of Physical Education in the New Normal Era) - Riadi, Okta; Satria, M. Haris (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2023)
The purpose of the study was to determine the level of physical fitness of students at the public elementary school 8 Semende Darat Laut (SDN 8 SDL) in the implementation of physical education in the new normal era of Covid-19. This study used a quantitative descriptive research design with a one-shot case study approach. The population in this study were 95 students of public elementary school 8 Semende Darat Laut (SDN 8 SDL), and the sample in this study were 45 students who were in grade 4, 5 and 6. The research instrument used was the indicators of the Indonesian Physical Fitness Test (TKJI) including 40 meters running, hanging and bending elbows, lying down for 30 seconds, vertical jump, and 600 meters running. The results of the study showed that the level of physical fitness of SDN 8 SDL students for all classes was in a very low condition (VL) with the final TKJI score ranging from 5-9.